Sex- and Age-Related Differences in Morbidity Rates of 2009 Pandemic Influenza A H1N1 Virus of Swine Origin in Japan - Eshima, Nobuoki (Public Library of Science, 2011)
BACKGROUND: The objective of the present study was to determine whether the morbidity rates of the 2009 pandemic influenza A H1N1 virus (pdmH1N1) varied by age and/or sex. METHODS AND FINDINGS: Retrospective analysis of 2,024,367 cases of pdmH1N1 was performed using the national surveillance data from influenza sentinel points in Japan. The male-to-female morbidity ratios (M/F ratios) in nineteen age groups were estimated as the primary outcome. The M/F ratios for pdmH1N1 influenza were: >1 in age groups <20 years and ≥80 years (p<0.001); <1 in age groups 20–79 years (p<0.001). This data suggests that males <20 years of age may be more likely to suffer from pdmH1N1 influenza than females in the same age categories. When the infection pattern for pdmH1N1was compared with that of seasonal influenza outbreaks between 2000 and 2008, the M/F ratio for pdmH1N1 influenza was higher in ages 3–29 years and lower in ages 40–79 years. Because the present study was based on the national surveillance, it was impossible to estimate the morbidity rate for the Japanese population. It is also likely that the data did not capture asymptomatic or mild infections. CONCLUSIONS: Although exposure to the pdmH1N1 virus is assumed to be similar in both boys and girls, M/F ratios were >1 in those younger than 20 years. The subsequent reversal of the M/F ratio in the adult generation could be due to several possibilities, including: greater immunity among adult males, more asymptomatic infections among males, less reporting of illness by males, or differences in exposure to the virus and probability of visiting a clinic. These results suggest that the infection and virulence patterns of pdmH1N1 are more complex than previously considered.